Who should pay for collecting taxes? : financing the IRS - Steuerle, C. Eugene (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1986)
After examining the ways the IRS is currently financed, Eugene Steuerle concludes that current methods give inadequate attention to both the benefits and the costs of tax administration. Steuerle finds not only that modest increases in funding are likely to bring in revenues well in excess of budgetary costs, but also that other mechanisms can improve the efficiency of the IRS without necessarily increasing costs. He focuses on the number and complexity of the programs the IRS is asked to administer and on the ways tax administrators are prevented from allocating resources for the most qualified personnel. The current budget process, he says, unnecessarily raises the costs of tax administration.
Includes bibliographies.
sju 22/01/2019
Loans
Keywords: Tax administration and procedure; Taxation; United States